Comparing the Six-Factor Model with Capital Asset Pricing Models in Explaining the Expected Investor Returns - javad ramezani; Yahya Kamyabi (فصلنامه پژوهش‌های اقتصادی ایران, 2017)
Successful investment requires identifying influential investment factors, its related risks and allocating optimal resources to obtain the highest returns. Individuals and institutional investors employ strategies to obtain additional return. One of these strategies is to determine the factors affecting risk and return in investment processes. This paper aims at examining the explanatory power of stock returns through the six-factor model and comparing Fama–French five-factor model, Carhart four-factor and Hou, Xue, Zhang (HXZ) q-factor models to determine the expected return on stocks of listed companies in Tehran Stock Exchange. Monthly data from the listed companies from  2002 to 2016 reveals  that Fama–French five-factor model can explain stock returns better than Carhart four-factor model and HXZ six subscales.  More importantly, adding momentum to the five-factor model did not increase the explanatory power. Also, the study showed that there were not significant results regarding Fama-french five-factor model of the value factor (HML) in Tehran Stock Exchange. Therefore, adding two factors of investment and profitability increases the explanatory power of the model.